High-latitude Southern Hemisphere fire history during the mid- to late Holocene (6000–750 BP) - Battistel, Dario; Kehrwald, Natalie M.; Zennaro, Piero; Pellegrino, Giuseppe; Barbaro, Elena; Zangrando, Roberta; Pedeli, Xanthi X.; Varin, Cristiano; Spolaor, Andrea; Vallelonga, Paul T.; Gambaro, Andrea; Barbante, Carlo (Climate of the Past, 2019)
We determined the specific biomass burning biomarker levoglucosan in an ice core from the TALos Dome Ice CorE drilling project (TALDICE) during the mid- to late Holocene (6000–750 BP). The levoglucosan record is characterized by a long-term increase with higher rates starting at ∼ 4000 BP and peaks between 2500 and 1500 BP. The anomalous increase in levoglucosan centered at ∼ 2000 BP is consistent with other Antarctic biomass burning records. Multiple atmospheric phenomena affect the coastal Antarctic Talos Dome drilling site, where the Southern Annular Mode (SAM) is the most prominent as the Southern Annular Mode Index (SAM A ) correlates with stable isotopes in precipitation throughout the most recent 1000 years of the ice core. If this connection remains throughout the mid- to late Holocene, then our results demonstrate that changes in biomass burning, rather than changes in atmospheric transport, are the major influence on the TALDICE levoglucosan record. Comparisons with charcoal syntheses help evaluate fire sources, showing a greater contribution from southern South American fires than from Australian biomass burning. The levoglucosan peak centered at ∼ 2000 BP occurs during a cool period throughout the Southern Hemisphere, yet during a time of increased fire activity in both northern and southern Patagonia. This peak in biomass burning is influenced by increased vegetation in southern South America from a preceding humid period, in which the vegetation desiccated during the following cool, dry period. The Talos Dome ice core record from 6000 to ∼ 750 BP currently does not provide clear evidence that the fire record may be strongly affected by anthropogenic activities during the mid- to late Holocene, although we cannot exclude at least a partial influence.